El Derecho a la remuneración puesto a prueba: análisis de la intervención unilateral del empleador en el salario en tiempos de pandemia - Sarzo Tamayo, Renato (2022)
This investigation analyzes the effects of the COVID-19 pandemic on the remuneration of workers, both from a quantitative and qualitative point of view. About the first, statistics are exposed and analyzed on how the salary behavior has been in times of pandemic. In relation to the second, two key issues that have been debated and are still being debated until now: i) is the unilateral reduction of remunerations as a result of the economic effects of COVID-19 on companies constitutional and legally possible?, ii) what is the limit for the compensation of the license with pay granted in the context of the pandemic? About it, this article uses legislation and doctrine (in both cases, national and comparative), as well as jurisprudence (both constitutional and administrative) to answer these two questions and, thus, formulate two rules about it.